2018
DOI: 10.1080/10826084.2017.1408328
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Neuropsychological Status during the Initial Phase of Abstinence in Alcohol Use Disorder: Neurocognitive Impairment and Implications for Clinical Care

Abstract: After completing acute detoxification, almost all participants (93%) were clinically impaired in at least one of the five cognitive domains at residential treatment entry, with one third of the sample impaired on ≥3 domains. Ten days later, 71% remained clinically impaired in at least one of five cognitive domains, with 29% of the sample impaired on ≥3 domains. Significant improvement over the 10-day period was observed for immediate memory, visuospatial abilities, and overall cognitive functioning. Clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…40,42 These cognitive functions are fundamental for AUD patients to benefit from psychosocial treatments during recovery because CBT and motivational interventions require preserved cognitive functions to be effective. 8,67,68 Our results showed that 70.73% of the total sample had impaired performance on at least one test of the neuropsychological battery items. These findings are in line with a study which found that, after completing acute detoxification, almost all participants (93%) were clinically impaired in at least one of the five cognitive domains at entry to residential treatment and 71% remained clinically impaired after 10 days.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…40,42 These cognitive functions are fundamental for AUD patients to benefit from psychosocial treatments during recovery because CBT and motivational interventions require preserved cognitive functions to be effective. 8,67,68 Our results showed that 70.73% of the total sample had impaired performance on at least one test of the neuropsychological battery items. These findings are in line with a study which found that, after completing acute detoxification, almost all participants (93%) were clinically impaired in at least one of the five cognitive domains at entry to residential treatment and 71% remained clinically impaired after 10 days.…”
Section: Discussionmentioning
confidence: 61%
“…These findings are in line with a study which found that, after completing acute detoxification, almost all participants (93%) were clinically impaired in at least one of the five cognitive domains at entry to residential treatment and 71% remained clinically impaired after 10 days. 68 This means that abstinence has a relevant role for neuropsychological functioning, but it is not the only factor since some individuals remained cognitively impaired.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite those severe forms, mild to moderate neurocognitive deficits are prevalent among patients with alcohol use disorder, with an estimated proportion of 50–70% presenting some degree of impairment (Bates et al, 2013). Even though for most of the patients many of the neuropsychological deficits related to heavy alcohol use are minimal or transient (Bates et al, 2013) and improve with sustained abstinence (Mulhauser, Weinstock, Ruppert, & Benware, 2018; Ridley et al, 2013; Ros-Cucurull et al, 2018; Stavro et al, 2013), in some cases, deficits are clinically severe and can persist (Hayes et al, 2016; Sachdeva et al, 2016). Nevertheless, the different cognitive functions do not recover homogeneously (Ioime et al, 2018; Mulhauser et al, 2018; Ros-Cucurull et al, 2018).…”
Section: Introductionmentioning
confidence: 99%